CALCULATED PHASE EQUILIBRIA FOR LOW- AND MEDIUM-PRESSURE METAPELITES IN THE KFMASH AND KMNFMASH SYSTEMS - Wei C.J.; Powell R.; Clarke G.L. (My University, 2004)
Petrogenetic grids in the KFMASH and KMnFMASH model systems calculated with the software thermocalc 3.1 are presented for the P-T range 0.5-12 kbar and 450-900 °C, for assemblages involving garnet, muscovite, chloritoid, biotite, chlorite, staurolite, cordierite, spinel, orthopyroxene, K-feldspar, Al2 SiO5 phases, quartz, water and melt. Based on calculated compatibility diagrams and P-T and T-M Mn [Mn/(Mg + Fe + Mn)] pseudosections for different metapelitic bulk compositions, the principal conclusions are that the addition of Mn to the KFMASH system: (i) enhances the stability of garnet, and, to a lesser extent, aluminosilicates; (ii) reduces the stability of staurolite, cordierite and, to a lesser extent, chlorite; and (iii) extends the medium pressure stability of muscovite and the low-P stability field of K-feldspar. The influence of Mn on individual mineral stabilities is strongly related to rock composition, in particular, to the relative contents of Al2 O3 and K2 O. For metapelites of a range of compositions and M Mn values, P-T pseudosections in the KFMASH system, in most cases, do not adequately predict the mineral assemblages observed in natural assemblages under medium and low-pressure conditions. In contrast, the P-T pseudosections in the KMnFMASH system generally provide more satisfactory results, suggesting that MnO is one of the non-KFMASH components that should not be neglected in documenting the phase equilibria of medium- and low-P metapelites.
Keywords: KFMASH AND KMNFMASH SYSTEMS; PHASE EQUILIBRIA; THERMO-CALC